SARS-CoV-2 precipitated Kasabach-Merritt syndrome in a child with angioma infantile and acute lymphoblastic leukemia: Case Report - Zarate, Vanessa (2021)
Background: We describe an 8-month-old boy with leukemia and SARS-CoV-2 infection who developed Kasabach-Merritt phenomenon. He had a positive SARS-COV-2 RT-PCR sample. Hematologic tests showed coagulopathy and intestinal involvement. She was managed in emergency receiving transfusion support and in hospitalization with social isolation measures, she started propanolol and corticotherapy as initial treatment of infantile angiomas. She presented with symptoms of intestinal obstruction and underwent surgery and evidence of hemorrhagic infarction with foci of intestinal ischemic necrosis, ending in ileostomy. We tried to understand a pathophysiological explanation of the dermatologic and gastrointestinal tract involvement by the virus and the atypical form of COVID-19. Given the emerging evidence of endothelial and vascular involvement in COVID-19, the development of tests to detect vascular lesions may be critical to guide the use of new therapeutic strategies.